Cover Picture: Transport of Nucleoside Triphosphates into Cells by Artificial Molecular Transporters (Angew. Chem. Int. Ed. 31/2018) - Zawada, Zbigniew; Tatar, Ameneh; Mocilac, Pavle; Buděšínský, Miloš; Kraus, Tomáš (Angewandte Chemie International Edition, 2018)
Transport of nucleoside triphosphates across cell membranes does not proceed under ambient conditions. In their Communication on page 9891 ff., T. Kraus et al. show rapid and selective transport of various fluorescently labeled nucleoside triphosphates (NTPs) into eukaryotic and prokaryotic cells by artificial transporters. The labeled NTPs, which are instantly released in the intracellular space, can be exploited for tracing metabolic processes such as DNA synthesis in live cells.